Effects of geomorphological processes and phytoclimate conditions change on forest vegetation in the Pomeranian Bay coastal zone (Wolin National Park, West Pomerania) - Tylkowski, Jacek; Paluszkiewicz, Renata; Winowski, Marcin; Czyryca, Paweł; Kostrzewski, Andrzej; Mazurek, Małgorzata; Rachlewicz, Grzegorz (Quaestiones Geographicae, 2023)
The functioning of plant associations, including forest associations, in the coastal cliff edge zone of the Pomeranian Bay in the Wolin National Park (WNP) is determined by short-term factors related to the dynamics of erosion and denudation processes and long-term phytoclimatic conditions’ changes. The study presents a temporary analysis of the occurrence of sea abrasion and water and aeolian erosion, based on the applied hydrometeorological threshold values. The influence of changes in phytoclimatic conditions on the development and productivity of coastal forests with the dominant species of Fagus sylvatica was also presented. Assessments of spatial susceptibility to erosion of the cliff coast and the existing plant associations were also carried out in conditions of the risk of coast erosion. It was found that 55% of the cliff edge zone of the Pomeranian Bay of the WNP and the forest associations (mainly Luzulo pilosae-Fagetum) occurring there are in the zone of particular risk of increased erosion and denudation processes. In addition, unfavourable trends in changes in phytoclimatic conditions in the 21st century were found, which reflect climate changes unfavourable to the development of beech forests on Wolin Island.